Identity and the Life Cycle - Erikson, Erik Homburger; Rapaport, David 1911-196 (New York : International Universities Press, 1968)
RAPOPORT (D.) : A Historical Survey of Psychoanalytic Ego Psychology
1. Ego Development and Historical Change, Clinical Notes
2. Growth and Crises of the Healthy Personality
3. The Problem of Ego Identity
bibliogr.